P183 Arterial stiffness was inversely associated with left ventricular diastolic function in indigenous Papuan populations - Ishida, A; Isotani, A; Fujisawa, M; Garcia Del Saz, E; Okumiya, K; Kimura, Y; Manuaba, I; Kareth, M; Rantetampang, A; Ohya, Y; Matsubayashi, K (European heart journal, 2020)
Abstract Background Age-related increase in systolic pressure is known to be absent in indigenous Papuan populations, partially because of their life-long low-sodium and high-potassium diets. Purpose The aim of this study was to investigate the age-related change in left ventricular (LV) systolic and diastolic function and the relationship with arterial hemodynamics among the indigenous Papuan highland people. Methods Indices of arterial hemodynamics were measured using oscillometric brachial cuff-based sphygmomanometer (Mobil-O-Graph). Brachial-ankle pulse wave velocity (baPWV) was measured using a semiautomatic device (form ABI/baPWV). LV systolic and diastolic function was evaluated by 2-dimensional echocardiography and tissue-Doppler imaging using Vivid iq. Results A total of 81 native Papuans (median age 42 years, 47% women) were enrolled in this study. None of the subjects took any medicines, particularly antihypertensive drugs. All participants presented in sinus rhythm. With ageing, LV mass index remained unchanged, and LV ejection fraction increased, but mildly reduced (40–50%) in 3 participants. Transmitral E-wave velocity slightly decrease but the change was not significant. Transmitral A-wave velocity markedly increased (ρ=0.60, P < 0.001) and E/A ratio decreased with age (ρ=-0.52, P < 0.001). Age-related change of E-wave deceleration time was not significant. Septal e′ (ρ=-0.60, P < 0.001) and lateral e′ decreased (ρ=-0.53, P < 0.001) and average E/e′ increased with age (ρ=0.44, P < 0.001). Left atrial volume index did not change significantly with age. In multivariate regression analysis, baPWV was independently associated with E/e" ratio both before and after adjustment for age, sex, body mass index, mean arterial pressure, and heart rate; however, indices of wave reflection including augmentation index and reflection magnitude were not associated with E/e′. Only age and heart rate were inversely associated with E/A ratio. Conclusion LV systolic function was preserved in indigenous Papuan populations; however, LV diastolic function decreased with ageing. Age-related arterial stiffening, not wave reflection, was inversely related to LV diastolic function.